2013
DOI: 10.5606/ehc.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Solitary spinous process metastasis: a case report

Abstract: Primary malignant tumors frequently metastasize to bone, third in frequency after liver and lung. [1] Breast, lung, prostate, and kidney cancers have been the most common malignancies with secondary spine involvement.[2] Breast and prostate cancers have particular clinical interest because of the prevalence of these diseases, with about 70% of the patients dying of these cancers having evidence of metastatic bone disease.[3] Bone metastases are also seen in carcinomas of the thyroid, kidney, and bronchus with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Posterior lumbar interbody fusion (PLIF) is a popular lumbar arthrodesis and posterolateral graft, and fixation can be easily added to PLIF to enhance spinal stability and to induce fusion. [6][7][8][9][10][11] Alteration of the biomechanics at the junction of fused and mobile segments is thought to accelerate degeneration in adjacent motion segments. Adjacent segment disease has been reported to occur in as many as 35% of patients following spinal fusion.…”
Section: Methodsmentioning
confidence: 99%
“…Posterior lumbar interbody fusion (PLIF) is a popular lumbar arthrodesis and posterolateral graft, and fixation can be easily added to PLIF to enhance spinal stability and to induce fusion. [6][7][8][9][10][11] Alteration of the biomechanics at the junction of fused and mobile segments is thought to accelerate degeneration in adjacent motion segments. Adjacent segment disease has been reported to occur in as many as 35% of patients following spinal fusion.…”
Section: Methodsmentioning
confidence: 99%
“…Algra et al 3 previously reported that the initial anatomic location of metastases within vertebrae was the posterior portion of the body based on their analysis of CT findings. When bone metastases exceptionally occur in the spinous processes, they could be confined to the posterior part of the vertebra without extending to the vertebral body 13 . An examination of the contours of spinous processes needs to be conducted in a routine radiographic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Metastases are in fact the most common malignant tumors of the sacrum with poor survival rates. [6] The most important predictor of local recurrence and survival for most common primary malign tumors (chordomas and chondrosarcomas) is a negative surgical margin. [7] Sacral bone infections are very rare manifestations of either hematogenous spread of an infection in the body or complication of an intra-abdominal operation.…”
mentioning
confidence: 99%